PEMODELAN STRUKTUR GEDUNG APARTEMEN GUNAWANGSA GRESIK MENGGUNAKAN SOFTWARE AUTODESK REVIT - Anggraini, Devi Fitria (Jurnal Vokasi Teknik Sipil, 2023)
BIM (Building Information Modeling) is a technological innovation in the era of the Industrial Revolution 4.0 that is used to plan, design, implement, and maintain buildings that can increase profits in planning smart buildings as well as increase effectiveness and efficiency in the construction process. One of the software products based on BIM (Building Information Modeling) is Autodesk Revit. The purpose of this study is to implement the BIM method in structural modeling using Autodesk Revit 2023 software in high-rise buildings that have the concept of mix-use high-rise buildings, namely Gunawangsa Gresik Apartment. The results of this study are in the form of 3D modeling, detailing, volume calculation, and visualization of structural work. In addition, the study analyzed the advantages and disadvantages of several aspects including software specifications, building structure modeling, modeling stages, detailed drawings, volume or quantity calculations, and time & human resources.